Penerapan Teori Classical Conditioning dalam Memperkuat Minat Belajar Siswa Sekolah Dasar Islam - Sari, Putri Sekar; Santosa, Sedya (SITTAH: Journal of Primary Education, 2024)
The present research aims to elucidate the application of Ivan Pavlov's Classical Conditioning theory by utilizing rewards to cultivate students' enthusiasm for studying. This investigation used a qualitative methodology with a case study design conducted at an Islamic Elementary School in Kotagajah, Central Lampung Regency. The data sources comprise multiple forms of evidence, such as interviews, observations, notes, narratives, and visual materials. The findings of this study suggest that using Classical Conditioning theory has consequences for establishing habits and changes in students. This phenomenon is marked by a surge in students' motivation, support, and enthusiasm towards studying. Each indicator of interest in learning, such as the desire for learning, feeling joyful and engaged in learning, active participation in learning, completion of assignments, attentiveness, and adherence to established norms, is evident.